Effects of forest fires on the permafrost environment in the northern Da Xing'anling (Hinggan) mountains, Northeast China. (14th August 2019) - Li, Xiaoying; Jin, Huijun; He, Ruixia; Huang, Yadong; Wang, Hongwei; Luo, Dongliang; Jin, Xiaoying; Lü, Lanzhi; Wang, Lizhong; Li, Wei'hai; Wei, Changlei; Chang, Xiaoli; et al.
Abstract: Forest fires have significantly impacted the permafrost environment, and many research programs looking at this have been undertaken at higher latitudes. However, their impacts have not yet been systematically studied and evaluated in the northern part of northeast China at mid‐latitudes. This study simultaneously measured ecological and geocryological changes at various sites in the boreal forest at different stages after forest fires (chronosequence approach) in the northern Da Xing'anling (Hinggan) Mountains, Northeast China. We obtained results through field investigations, monitoring and observations, remote sensing interpretations, and laboratory tests. The results show that forest fires have resulted in a decreased Normalized Difference Vegetation Index (NDVI) and soil moisture contents in the active layer, increased active layer thickness (ALT) and ground temperatures, and the release of a large amount of C and N from the soils in the active layer and at shallow depths of permafrost. NDVI and species biodiversity have gradually increased in the years since forest fires. However, the vegetation has not fully recovered to the climax community structures and functions of the boreal forest ecosystems. For example, ground temperatures, ALT, and soil C and N contents have been slowly recovering in the 30 years after the forest fires, but they have not yet been restored to pre‐fire levels. This study provides important scientific bases for assessment of the impacts of forest fires on the boreal forest ecosystems in permafrost regions, environmental restoration and management, and changes in the carbon stock of soils at shallow (<3 m) depths in the Da Xingan'ling Mountains in northeast China.